2017
DOI: 10.1371/journal.pone.0182688
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of WHO criteria for identifying ART treatment failure in Vietnam from 2007 to 2011

Abstract: ObjectiveWe evaluated the sensitivity and specificity of the WHO immunological criteria for detecting antiretroviral therapy (ART) treatment failure in a cohort of Vietnamese patients. We conducted a stratified analysis to determine the effects of BMI, peer support, adherence to antiretroviral (ARV) drugs, age, and gender on the sensitivity and specificity of the WHO criteria.MethodsWe conducted a retrospective cohort study of 605 HIV-infected patients using data previously collected from a cluster randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(25 reference statements)
1
6
0
Order By: Relevance
“…This result follows the elevated HIV incidence in PWID in Vietnam [1] and is in line with previous findings [21,22]. Patients newly initiating ART were essentially men, a finding also highlighted in other studies in Vietnam [6,[23][24][25][26]. This is partly explained by the large representation of PWID in this study; nearly all PWID were male, as previously reported [27].…”
Section: Plos Onesupporting
confidence: 93%
See 1 more Smart Citation
“…This result follows the elevated HIV incidence in PWID in Vietnam [1] and is in line with previous findings [21,22]. Patients newly initiating ART were essentially men, a finding also highlighted in other studies in Vietnam [6,[23][24][25][26]. This is partly explained by the large representation of PWID in this study; nearly all PWID were male, as previously reported [27].…”
Section: Plos Onesupporting
confidence: 93%
“…In 2017, it was estimated that about one third of those on ART received viral load testing in Vietnam [5]. This is particularly important as the immunological and clinical criteria to diagnose therapeutic failure have been shown to perform poorly [6][7][8]. Laboratories currently able to perform viral load measurements are concentrated in the large urban centers of Hanoi and Ho Chi Minh City, while HIV patients are spread all over the country.…”
Section: Introductionmentioning
confidence: 99%
“…Though it is found that the WHO immunological criteria have a very low sensitivity and high specificity (42), this finding showed that HIV treatment failure using immunological definition of treatment failure (10.2%) was higher than that of using clinical (6.3%) and virological (5.6%) definition of treatment failure. These variations might be due to the number of studies included to immunological definition of HIV treatment failure were many in number.…”
Section: Discussionmentioning
confidence: 77%
“…Though the WHO immunological criterion is a very low sensitivity and high specificity test [40], this finding showed that HIV treatment failure was higher (10.2%) when the immunological definition used than that of clinical (6.3%) and virological (5.6%) treatment failure. This variation might be due to studies included in the immunological definition of HIV treatment failure were more than studies used to pool the clinical and virological failure.…”
Section: Discussionmentioning
confidence: 79%